FLIPGRID:Learning Based-Application Towards Speaking Class - Lubis, Rica Umrina; Siregar, Indra Kurniawan (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
In this study, 60 English Education Department of STAIN Mandailing Natal students were offered to use Flipgrid, as a tool during online distance learning in order to enhance students’ communication and discussion in the presence of these learning activities including speaking lesson. This study focuses on students’ responses in operating flipgrid as a creative and interesting tools that centered on speaking skill. The study was qualitative method. The instruments of this research was used questionnaires and interview. The result of this study showed that there were 16 positive response from the interactive features, accessibility, psychological fulfillment and connectivity and 8 negative responses towards Flipgrid application start from equipment, competitiveness and originality. The highest positive responses was easy to use. Meanwhile the negative responses found some obstacles in uploading process. It can be concluded that the flipgrid provided creative and interesting tools for speaking and helped students to adapt in pandemic condition.